Evaluation of Internal Audit Function in Detecting Skimming Fraud at PT ABC - Putri, Nanda Meidiana; Siregar, Sylvia Veronica Nalurita Purnama (E-Jurnal Akuntansi, 2025)
Fraud is a type of skimming that poses a serious threat to companies in the financing sector, including PT ABC, due to its impact on finance, reputation, and law. Internal audits play an important role in detecting and preventing skimming fraud, but their effectiveness in financing companies has not been widely explored. This study aims to evaluate the effectiveness of PT ABC's internal audit function in detecting and preventing skimming fraud. Thematic and structural narrative analysis approaches were used, with primary data obtained through semi-structured interviews with PT ABC's internal auditors. The results of the study indicate that the internal audit function at PT ABC effectively detects and reduces skimming fraud, as seen from the decrease in the number of cases from 55 at the end of 2023 to 22 cases in September 2024, as well as the reduced loss value. Implementing strict policies, using COLLAR technology, and a global standards-based audit strategy play an important role in achieving these results. Keywords: Internal Audit; Fraud Prevention; Internal Control; Skimming Fraud